2020
DOI: 10.1088/1757-899x/864/1/012199
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Magnetohydrodynamic Blood Flow through an Artery with Multiple Stenosis

Abstract: The study theoretically accounts for the impact of Magnetohydrodynamics on streaming blood through an artery having multiple stenosis regions using the non-Newtonian Cross-rheological model. It is regarded that the streaming blood is unsteady and pulsative. The use of appropriate conditions is predicated on the assumption that the flow is laminar and axisymmetric which makes the problem two-dimensional. The geometry of stenosis was immobilized into a rectangular grid using the radial coordinate transformation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This comparative study revealed that irregular symmetric stenosis exhibits a higher microrotation than bell-shaped stenosis in micropolar fluid and hybrid nanofluid. Joshua et al (2020) comprehensively investigated unsteady blood flow characteristics in an inclined multiple stenosis configuration. The study encompassed the manipulation of numerous crucial parameters, precisely the Hartmann number, severity of stenosis, Power Law index, and Reynolds number.…”
Section: Introductionmentioning
confidence: 99%
“…This comparative study revealed that irregular symmetric stenosis exhibits a higher microrotation than bell-shaped stenosis in micropolar fluid and hybrid nanofluid. Joshua et al (2020) comprehensively investigated unsteady blood flow characteristics in an inclined multiple stenosis configuration. The study encompassed the manipulation of numerous crucial parameters, precisely the Hartmann number, severity of stenosis, Power Law index, and Reynolds number.…”
Section: Introductionmentioning
confidence: 99%